Pengembangan Kesadaran Kesehatan Remaja Melalui Program Remaja Sehat Peduli Sesama di SD Negeri 101778 Medan - Usiono Usiono; Putri Aulia Sitorus; Rini Anggraini Br Siregar; Salsabila Putri Wibowo (Jurnal Medika Nusantara, 2024)
Healthy teenagers CARE FOR PEOPLE is a program implemented at SD Negeri 101778 Medan. This program aims to increase adolescent awareness about the importance of health and caring for others. This program is implemented through various activities, such as health education, cleanliness competitions, and social service activities. The evaluation results show that this program has succeeded in increasing teenagers' awareness about the importance of health and caring for others. This can be seen from the increasing knowledge of teenagers about health, the increasing participation of teenagers in hygiene activities, and the increasing concern of teenagers for each other. This program can be an example for other schools in increasing youth awareness about the importance of health and caring for others.